Do I deserve to belong? Migrants' perspectives on the debate of deservingness and belonging. Issue 17 (13th December 2021) - Blachnicka-Ciacek, Dominika; Trąbka, Agnieszka; Budginaite-Mackine, Irma; Parutis, Violetta; Pustulka, Paula
ABSTRACT: The notion of belonging, prominent in social sciences, has been recently used extensively in relation to Central Eastern European migrants in the UK. Whereas the Brexit debates on migration have spotlighted the macro-politics of belonging and the judgments on who deserves to stay and under which conditions, the question of how these discourses of 'deservingness' surrounding Brexit may influence the everyday and intimate aspects of belonging among migrants warrants further exploration. Drawing on the interviews with 77 young Polish and Lithuanian migrants in the UK conducted from 2019 to 2020, this article examines how migrants position themselves in relation to the discourses of deservingness and hierarchies of desirability. The focus is also placed on how they negotiate their strategies of (un)belonging to the British society. We argue that the prominence of the deservingness discourse – which has gained momentum in Brexit Britain - entraps migrants in the constant process of boundary making and may prevent them from ever feeling part of the 'community of value'.